Reconstructing cognitive levels of test items in Indonesian Textbook for vocational school - Saragih, Erikson; Sinulingga, Samuel; Bukit, Bethesda; Wiranata, Vanny (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Although there have been a lot of studies on Bloom's taxonomy's use in the evaluation of language learning in Indonesia, there has never been any research on Bloom's taxonomy's use in the training and evaluation content of Indonesian language textbooks in vocational schools. The objectives of this study are to describe the reading material, cognitive level, and relationship between the material and other aspects in forty items of reading material from Indonesian language textbooks for vocational schools. To achieve this goal, this research uses descriptive qualitative research methods with content analysis design using primary data sources from textbooks. The results of this qualitative study using a content analysis design revealed that the choice of reading material topics is very diverse and represents textual genres. The level of cognition is not evenly distributed and is dominated by Lower Order Thinking Skills (LOTS) with a total of 24 questions (60%), and there are even 2 levels of cognition that are not accommodated at all. The findings of this study defined the distribution of the level of understanding of the items in the textbook, which is very useful for Indonesian language teachers and textbook writers to complete the items evenly according to the level of cognition dispersal, ensuring that students' mastery of the subject matter is broad.